2021
DOI: 10.1002/ccr3.4170
|View full text |Cite
|
Sign up to set email alerts
|

Levothyroxine sodium oral solution to control thyroid function in a patient with hypothyroidism and celiac disease

Abstract: Implementing a gluten-free diet and switching to the levothyroxine oral solution significantly improved malabsorptive and hypothyroid symptoms in a patient with hypothyroidism, Addison's disease, and celiac disease without the need to increase levothyroxine dosage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Liquid LT4 has previously ameliorated impaired absorption issues, including in 8 patients with lactose intolerance whose TSH levels normalized when switched from LT4 tablets to LT4 liquid formulation [ 17 ]. Further, a case study reported that symptoms resolved and TSH levels stabilized in a patient with Hashimoto's thyroiditis and celiac disease following the switch from LT4 tablets to LT4 liquid formulation and a gluten-free diet [ 31 ]. Another case study found that switching a patient with Hashimoto's disease, gastroparesis, and small intestinal bacterial overgrowth to LT4 liquid formulation from compounded T4/T3 achieved TSH levels within the optimal range with resolution of symptoms [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liquid LT4 has previously ameliorated impaired absorption issues, including in 8 patients with lactose intolerance whose TSH levels normalized when switched from LT4 tablets to LT4 liquid formulation [ 17 ]. Further, a case study reported that symptoms resolved and TSH levels stabilized in a patient with Hashimoto's thyroiditis and celiac disease following the switch from LT4 tablets to LT4 liquid formulation and a gluten-free diet [ 31 ]. Another case study found that switching a patient with Hashimoto's disease, gastroparesis, and small intestinal bacterial overgrowth to LT4 liquid formulation from compounded T4/T3 achieved TSH levels within the optimal range with resolution of symptoms [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although liquid LT4 formulation safety and efficacy has been investigated in numerous studies and clinical scenarios, this is one of the first reports on the new, alcohol-free liquid LT4 composition, containing only L-thyroxine, glycerol, and water. To date, outcomes of therapy with alcohol-free liquid LT4 have been described in a single-centre study in patients with primary and central hypothyroidism [14] and case studies concerning a newborn with congenital hypothyroidism and 21 trisomy [37], a patient with celiac and Addison's disease [38], patients with celiac disease, a pregnant pa-tient with post-operative hypothyroidism, a patient with post-operative hypothyroidism due to Graves' disease [39], and in a patient with malabsorption due to multiple gastrointestinal disorders [40]. Our results seem to be in line with the previous reports, suggesting potential benefits of treatment with novel LT4 formulation.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Malabsorption in addition to celiac disease (CD) has been reported in AD patients; CD is an immune-mediated small intestinal disease affecting both children and adults, with a general prevalence in the general population of 0.5–1%; the diagnosis is based on clinical, serological assessments and small intestinal biopsies [ 146 , 147 , 148 ]. CD is associated with other autoimmune diseases: most often type 1 DM in children and teenagers and autoimmune thyroid disorders (mostly hypothyroidism) in adults, but also autoimmune types of AD, hepatitis, hypoparathyroidism, hypopituitarism, premature ovarian failure, etc.…”
Section: Methodsmentioning
confidence: 99%